Pengaruh Interaksi Live Streaming Dan Potongan Harga Terhadap Minat Beli Pada Konsumen E-Commerce Tiktok Shop Wilayah Jakarta Barat: The Effect of Live Streaming Interaction and Discounts on Purchasing Interest Among E-Commerce Consumers on TikTok Shop in West Jakarta - Azzahra, Chindy Zaliva; Lestari, Tri (CV Warnak Johanna Nusantara, 2026)
Changing consumer behavior in the digital era is driving a shift from traditional shopping to interactive online platforms. TikTok Shop is growing rapidly through live streaming commerce innovations that enable direct interaction between sellers and buyers, creating a personalized shopping experience while increasing trust and the urge to buy. The purpose of this study is to determine how live streaming (X1) and discounts (X2) affect purchase interest (Y) customers of TikTok Shops in Jakarta Barat. The methodology used in this study is quantitative and employs the purposive sample technique, conducting a survey with 150 participants who are selected based on specific criteria, namely those who live in Jakarta Barat, have previously participated in live streaming, and have visited or expressed interest in working at the TikTok Shop in the final month. Data analysis is carried out using the SPSS version 24 application and linear regression analysis. The results of this study indicate that live streaming (X1) has a positive and significant impact on purchase interest, with a thitung value of 2,912 that is greater than the ttabel of 1,976 and a significance level of 0.005. discounts (X2) also indicates a positive and significant impact with a thitung of 7,581, which is higher than the ttabel of 1,976 and has a significance level of zero thousand. Together, these two variables have a significant impact on purchase interest, as indicated by the Fhitung value of 76,655, which is higher than that of Ftabel 3.06, and the R2 value of 0.511. Based on the aforementioned results, it can be concluded that a communication-based live streaming strategy and a price-based pricing strategy are effective in increasing customer purchase intent at TikTok Shops.